The Role of Private Sector to Support Special Region of Yogyakarta’s Craft Product Export to the Global Market - Shanti Darmastuti; Sri Issundari; Mansur Juned; Nazaruddien Agus Salim Putra Angkotasan (Lembaga Kajian Demokrasi dan Pemberdayaan Masyarakat (LKD-PM), 2022)
As international trade flows, businesses aim to expand their market to the global market. One of Indonesia’s flagship industries in trade is the creative industry, in which handicrafts are produced. Handicrafts have been Yogyakarta’s (officially, the Special Region of Yogyakarta) featured product for export. The government has tried many efforts to increase the chance of accessing the global market with the handicrafts, such as holding exhibitions and building capacity for the craftsmen. Not only the government but also the private sectors are supporting the effort. This study aims to visualize and analyze the role of the private sector in improving the local and global craft markets. We conducted interviews from May to October 2022 with Yogyakarta’s government and private sectors to obtain primary data. We also used document analysis to supplement the interviews' analysis. Results show that the role of the private sector, both when working independently and in partnership with the government, is important in supporting the export of Yogyakarta’s craft products. However, the study also found that there are some challenges that need to be solved to optimize the private sector’s role. Therefore, future studies can be focused on private sector strategies for addressing challenges in export activities.